Kesan personaliti proaktif dan sokongan organisasi ke atas pembangunan kerjaya terhadap prestasi pekerja di Suruhanjaya Syarikat Malaysia (SSM) Kuala Lumpur Sentral, Kuala Lumpur - Baharum, Mohamad Hafizan (2013)
This research was conducted at Suruhanjaya Syarikat Malaysia Kuala Lumpur Sentral, Kuala Lumpur. Objective of this study is to identify relationship between proactive personality and employee performance, to identify relationship between organization support on career development and employee performance, to identify relationship between career management behavior and employee performance, to identify mediating effect of career management behavior in relationship of proactive personality and employee performance and to identify mediating effect of career management behavior in relationship of organization support on career development and employee performance. The data was collected from 252 respondents by using questionnaire were distributed to staff at Suruhanjaya Syarikat Malaysia Kuala Lumpur Sentral, Kuala Lumpur. The data were analyzed using SPSS version 18.0. The data were analyzed using descriptive method, Pearson correlation, and hierarchical regression. The findings revealed that proactive personality has significant relationship with employee performance beside that, organization support on career development has not significant relationship with employee performance. Significant relationship also showed between proactive personality and career management behavior and organization support on career development has not significant relationship with career management behavior. Result from analysis showed that career management behavior has positive and significant mediating relationship in relation of proactive personality and employee performance. Other than that, mediating relationship of career management behavior has not significant in relationship of organization support on career development and employee performance